What Evil Felled the Duke? A Re-examination of the Death of the 4th Duke of Richmond - Whitney, Hugh (Ontario History)

(untitled) (The Ontario Historical Society, 2013)
Charles Lennox, the 4th Duke of Richmond, was Governor-in-Chief of British North America from 1818-1819. His death in Richmond (Upper Canada) is usually attributed to rabies contracted from a tame fox that he had encountered two months prior to his death. Though rabies may have been the cause of his death, the sources of information for most historical writings on the subject are limited to official accounts and give no insight into the known character of the Duke. This article provides an alternative explanation for the death of His Grace.